Book review: Manoranjan Byapari, Interrogating My Chandal Life: An Autobiography of a Dalit. Issue 2 (November 2019) - Sarangi, Jaydeep
Manoranjan Byapari, Interrogating My Chandal Life: An Autobiography of a Dalit (translated by Sipra Mukherjee). Kolkata: Sage-Samya, 2018, ₹550, 356 pp. (paperback). ISBN: 9381345139, 9789381345139.